Intravenous rt-PA for acute stroke: comparing its effectiveness in younger and older patients. Issue 9 (16th August 2005) - Mouradian, M S; Senthilselvan, A; Jickling, G; McCombe, J A; Emery, D J; Dean, N; Shuaib, A
Abstract : Objective: To study the short and long term differences in outcome between patients ⩾80 years of age and those ⩽79 years of age who received intravenous recombinant tissue plasminogen activator (iv rt-PA) for acute stroke within the first 3 hours of symptom onset. Methods: We studied consecutive patients treated with iv rt-PA for acute stroke, with prospective follow up of up to 3 years. Outcome measures included National Institutes of Health Stroke Scale (NIHSS) score, Barthel Index (BI), modified Rankin score (MRS), and stroke mortality. Patients were split into two groups: younger (⩽79 years) and older (⩾80 years). Results: There were 65 patients in the younger cohort and 31 patients in the older. Older patients were more likely to present with more severe baseline stroke (p = 0.04; odds ratio (OR) 3.04; 95% confidence interval (CI) 1.03 to 8.98). Stroke mortality at 90 days was 10.8% in the younger and 32.3% in the older cohort (p = 0.01). At 90 days' follow up, patients in the older cohort with more severe stroke (NIHSS score ⩾11) were nearly 10 times more likely to have poor outcome compared with their younger counterparts presenting with severe stroke (p = 0.001; OR = 10.36; 95% CI 2.16 to 49.20). Baseline stroke severity and age were the only independent and equal predictors for stroke outcome. No threshold was found for age or baseline stroke severity predicting outcome. Conclusion: Older patients presenting with more severe baseline stroke are much less likely to benefit from iv rt-PA as compared with their younger counterparts.